Dimensions responsible for overall satisfaction among university students: a case study of Ibn Haldun university - Nazir, Thseen (Сибирский психологический журнал)
Educational institutions around the world are always trying to impart the highest quality of education, and they are continuously improving their quality and standards. This practice enables them to attract much more capable students as well as academics. As the student is at the center of the learning process, his/her satisfaction is also at the center of the quality and standards of an educational institution. This study aims to find and assess the most important dimensions responsible for the overall satisfaction of Ibn Haldun's students. For this, a sample of 180 students from different departments, programs (undergraduate, graduate and language), gender (Male - 41.28% and Female - 58.72%), nationalities (Turkish - 71% and Foreigners - 29%), etc. were surveyed. Students were questioned about their satisfaction levels on different dimensions like academic, accommodations, facilities and services, extracurricular, economic and financial, social and cultural via their expectations before joining Ibn Haldun University. In-depth descriptive statistical analysis and multiple linear regression model with General to Specific methodology has been used to find and evaluate the key dimensions contributing to overall satisfaction. The study found overall satisfaction to be independent of gender and nationality. Also, graduate students were found to be more satisfied than undergraduates, while the number of semesters spent at Ibn Haldun University was found to be positively and highly correlated with overall satisfaction. Furthermore, economic and financial benefits granted to students by the university, academic features and the facilities and services dimen-sions are the key determinants of overall satisfaction of the students. The study concludes that the students' satisfaction can be further improved by enhancing the above-mentioned features and a special attention may be given to social and cultural integration of students, accommo-dation facilities provided to the students and extracurricular activities.